2018
DOI: 10.1002/jcb.27767
|View full text |Cite
|
Sign up to set email alerts
|

Roles for osteocalcin in proliferation and differentiation of spermatogonial cells cocultured with somatic cells

Abstract: Spermatogonial cells (SCs) are key cells for spermatogenesis. These cells are affected by paracrine signals originated from nearby somatic cells, among them Leydig cells have receptors for osteocalcin, a hormone known for exerting positive roles in the promotion of spermatogenesis. The aim of this study was to evaluate roles for osteocalcin on SCs proliferative and differentiation features after coculture with Leydig cells. SCs and Leydig cells were isolated from neonate NMRI offspring mice and adult NMRI mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…After enzymatic digestion and differential platting, the SSCs were identified by ID4 and Thy1 surface markers. Several studies have reported that ID4 expression is limited to A s spermatogonia and overexpression of ID4 inhibits the stem-to-progenitor transition [ 37 , 38 ]. In fact, ID4 plays a key role in the regulation of SSCs’ self-renewal or undifferentiated state.…”
Section: Discussionmentioning
confidence: 99%
“…After enzymatic digestion and differential platting, the SSCs were identified by ID4 and Thy1 surface markers. Several studies have reported that ID4 expression is limited to A s spermatogonia and overexpression of ID4 inhibits the stem-to-progenitor transition [ 37 , 38 ]. In fact, ID4 plays a key role in the regulation of SSCs’ self-renewal or undifferentiated state.…”
Section: Discussionmentioning
confidence: 99%
“…Quality of PCR reactions was determined by a melting curve analysis with β-actin used as a reference gene. Cycle threshold (Ct) of the reference gene was subtracted from Ct of the target gene to obtain ΔCt after which ΔΔCt was calculated to measure the relative expression of the desired genes [ 35 ]. Sequences of the primers used are given in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…First, the testes were suspended in 3 mL Dulbecco modi ed Eagle medium (DMEM) containing 5 µg/mL DNase (Sigma-Aldrich, Germany), 1 mg/mL collagenase type IV (Gibco, CA) and 1 mg/mL hyaluronidase (Sigma-Aldrich). Then, they were transferred to an incubator for 20 min at 37°C until forming a cellular suspension [20]. Interstitial cells were digested after pipetting and centrifuging at 15×g for 5 minutes.…”
Section: Testicular Surgery Ssc Isolation and Enrichmentmentioning
confidence: 99%